Carollia perspicillata (Chiriptera, Phyllostomidae) de ocorrência no Estado do Maranhão: um enfoque morfológico e molecular - Mascarenhas, Márcia de Jesus Oliveira (2017)
The species Carollia perspicillata, a frugivorous bat, belongs to the genus Carollia family Phyllostomidae. This is quite abundant in tropical environments and has great potential in seed dispersal, given its food habit. Commonly bats of this genus Carollia have been classified as a species complex due to their great similarity. Studies with morphological and molecular data have been applied in order to know this fauna so little studied. In this context, the objective was to identify the species C. perspicillata and to report its population dynamics in the state of Maranhão, using morphometric, craniometric and molecular data. Samples of C. perspicillata were collected in the municipalities of Caxias, Carutapera, Godofredo Viana, Turiaçu, Cândido Mendes, Chapadinha, Codó, Urbano Santos, São Luís and Vargem Grande. The morphometric and craniometric measurements were measured with the aid of a digital caliper. A total of 39 measures were analyzed in the BioEstar and Statistic software. Total DNA was extracted using the Wizard Genomic DNA Purification kit from Promega. The mitochondrial genes COI and 16S rRNA were amplified via PCR and sequenced sequentially. For the analysis of the molecular data, we used the software: BioEdit, DAMBE, MEGA, DNAsp, NETWORK, BAPS and ARLEQUIN. The morphological results together with the molecular indicated the occurrence of a single specific status C. perspicillata in the state of Maranhão, however, but the molecular data allowed to verify the existence of up to three lineages. Therefore, these data reinforce the need for a taxonomic revision in this group.